Behavioral Outcomes in Children With an Orofacial Cleft in a National Study in New Zealand. (August 2021) - Thompson, John M. D.; Ayrey, S. Louise; Slykerman, Rebecca F.; Stone, Peter R.; Fowler, Peter V.
Objective: To determine whether children with an orofacial cleft have higher levels of behavioral problems than the general population and whether this differs by cleft phenotype. Design: A cohort of children with cleft lip and/or palate (CL/P) born in New Zealand from January 1, 2000. Setting: Cleft clinics in New Zealand participating in a larger outcomes study between 2014 and 2017. Participants: Children (N = 378) aged 5 to 12 years of age and their parents. Main Outcomes: The Strengths and Difficulties Questionnaire (SDQ) and Pediatric Quality of Life Inventory (PedsQL) Generic Core Scales 4.0 and Family Impact Module 2.0. Results: Compared to standardized norms, children with a cleft had higher than expected (defined as 20%) levels of abnormal/borderline SDQ scores for conduct problems (27.4%, P = .0003) and peer relationship problems (31.6%, P < .0001) but lower than expected levels of problems with pro-social skills (6.3%, P < .0001). There were no significant differences by age-group and or cleft phenotype other than an increased risk of hyperactivity in children with CP compared to children with CL. Total difficulties SDQ scores had moderate correlations with the PedsQL. Conclusions: While over 90% of children with CL/P had normal prosocial skills, they may not be easily accepted by their peers which may result in behavioral problems. These concerns were moderately related to lower quality of life. Support for establishment and maintenance of peer relationships is important to address externalizing and peer difficulties in children with CL/P. Community knowledge and understanding of CL/P needs to continue to be promoted.